ANALISIS KUALITAS DAN KETAHANAN LUNTUR WARNA BATIK HASIL PROSES REUSE SISA LARUTAN CELUP ZAT WARNA SINTETIS GOLONGAN BEJANA MENUJU GREEN INDUSTRY - Maghfiroh Maghfiroh; Mutadin Mutadin; Sri Puji Astuti (LPPM Universitas Pekalongan, 2020)
It has been found the fact that natural dyes are not environmentally friendly dyes if they are directly discharged into the water without undergoing processing. Theoretically, both synthetic dyes and natural dyes have the same opportunity to cause pollution of aquatic ecosystems because they have the same functional groups. So far, natural dyes are considered environmentally friendly not because of the low waste pollutant parameters, but because there is a process of reuse of the remaining dyed water. The process of reusing the remaining dye solution can reduce the volume of liquid waste discharged into the water. This study aims to reuse of the remaining water dyed synthetic of vat dyes for the process of making batik. The quality of the staining results is evaluated by color fastness test on washing and rubbing. The reusing synthetic of vat dyes group is done for coloring cotton fabrics. The fabric color evaluation stage is carried out to test the color intensity and fastness of synthetic dyes of vat dyes group if the dye is reused in the batik process. Color intensity test was carried out by UV-PC spectrophotometer, color fastness test on washing use gray scale, and color fastness test on dry rubbing use staining scale. Based on the color intensity test, the process of reusing the remaining dye solution of the indantren navy blue R is still optimal if used on the same day. Reusing the remaining dye solution the next day gives a large value of color intensity value from the use of the dye solution for the first time. Indantren navy blue R color substances are relatively resistant to hydrolysis reactions during the dissolution process in water.